Prevalence of Sleep Disorders And Its Association With Socio-Demographic Variables Among Elderly People of Bardiya District, Nepal (Voice: A Biannual & Bilingual Journal, 2023)
Sleep disorders constitute a substantial public health concern in an ageing society. It encompasses any disruption in the quantity or quality of sleep. This research aims to ascertain the prevalence of sleep disorders and its association with socio-demographic variables among the elderly residing in the Bardiya district of Nepal. A descriptive cross-sectional research design was adopted for the study. This study relies entirely on primary data, and a sample of 60 elderly people from community of Mainapohar-06, Badhaiyatal, Bardiya, Nepal was selected using simple random sampling method. The data were analyzed employing descriptive and inferential statistics through software (SPSS version 21). The findings of the research revealed that 75% of the sixty elderly had sleep disorders, while 25% did not, and 38.3% of them had daily trouble getting off to sleep. Among the various factors; gender, health condition, and educational status have a statistically significant association with sleep disorders. It can be inferred that a majority of the participants experienced sleep disturbances, thereby exposing themselves to more severe physical and mental health consequences.